The Farewell Address Of Prophet Muhammad: A Universal Declaration Of Human Rights - Yusuf, A. A.; Ishola, A. (Universiti Sains Islam Malaysia, 2024)
A critical examination of the farewell address of Prophet Muhammad during his pilgrimage in the 7th'century reveals that the pronouncements made therein pass messages on conducts that cuts across various sectors of human values and attitudinal characteristics. Though, the address was delivered hundreds of years before the United Nations Universal Declaration on Human Rights in 1948, but it is, however, acknowledged as a significant and valuable human rights codes ever bequeathed to mankind, in the sense that the majority of issues on human rights that are now universally celebrated and jealously guided, such as rights to life, property, dignity, freedom from discrimination, rights of the women, to mention but a few, were taken from this address. Thus, the address deserves a special examination to appreciate the rubric of thought provoking issues raised by the Prophet as they are found to inure to the advancement of human rights in the contemporary era. To this end, this paper examines the various human rights issues raised in the address with the aim of comparing it with the modern human rights declarations. The conclusion drawn from the study is that, without an in-depth understanding of the messages of this farewell address, a study of human rights in International law cannot be said to have been completed. Also, any modern study on the historical foundation of human rights declaration will be missing a significant landmark period without objective consideration and reference to this historic farewell address.